Interprofessional clinical simulation in enhancing patient centered care competency among Indonesian nursing students: A mixed methods design - Galih Jatnika; Jordan Tovera Salvador (Jurnal Keperawatan Padjadjaran, 2025)
Backgrounds: Nursing clinical simulations to improve patient centered care (PCC) competency are currently often limited to nursing students. Interprofessional clinical simulations are designed to improve PCC competency by involving students from various health professions, including medicine, physiotherapy, nutrition, and medical laboratory technology. Purpose: This study aimed to identify the effect of interprofessional clinical simulation on patient centered care competency. Method: This research used a convergent parallel mixed methods design. The quantitative study involved 50 respondents, and the qualitative study involved 9 participants. Two case scenarios were given in the simulation. The instrument was used patient centered care competency scale. Quantitative data were analyzed using the Wilcoxon test, qualitative data using thematic analysis, and the two data sets were integrated using a joint display table. Result:  Quantitative results showed a significant effect of the interprofessional clinical simulation in enhancing PCC competency (p<0.001). Qualitative findings identified four themes and fourteen subthemes. The themes are valuing and honoring the patient's viewpoint, ensuring patients are fully engaged in their treatment plan, addressing the patient's discomfort for peace and well being and protecting the patient's rights and needs. The integration of the two data showed that the quantitative research results converged with the qualitative research results. Conclusion: The results of the increase in PCC competency scores converged with most themes and subthemes from nursing student’s experiences.